Ametropías y su influencia en el rendimiento laboral del personal de las Fuerzas Armadas que asisten al Centro de Salud Ala de Combate nro.21, Guayas -Yaguachi, diciembre 2022- mayo 2023. - Brunis Proaño, Magaly Magdalena (2023)
Introduction: The work responds to the need to investigate the influence that ametropias have on the work performance of Armed Forces personnel who attend the Ala de Combate No. 21 Health Center. Since these conditions are a public health problem worldwide and directly influence the quality of life of human beings. Objective: To determine the influence of ametropia on the work performance of Armed Forces personnel who attend the Ala de combate Nro.21 health center, Guayas - Yaguachi, December 2022- May 2023. Methodology: the present investigation, according to the level, responds to the descriptive one, is of an analytical cross-sectional type characterized by documentary and field design, and uses the deductive and inductive method with the use of observation, interview, analysis and visual evaluation techniques. Directly for the collection of the required information. Results: After the respective visual evaluation of each one of those involved in this research project, it was detected that 20% of those evaluated present myopia; 3% farsightedness; 3% astigmatism and 13%; 20% have myopia and astigmatism; 3% hyperopia with astigmatism; 7% myopia and presbyopia; 7% hyperopia and presbyopia; 3% astigmatism and presbyopia; 10% myopia, astigmatism and presbyopia, finally the remaining 10% present hyperopia, astigmatism and presbyopia. Conclusion: The study shows that 100% of the population presented ametropia and indicated that during their work activities they experienced symptoms such as blurred vision near and far, distorted vision, headache, eye pain that directly influenced the fulfillment of their work activities, since that generates deconcentration, complexity, demotivation, fatigue among other factors that decrease work performance and does not allow 100% performance.